Julio Medem. - Stone, Rob (Spanish and Latin American Film Makers., 2007)
This thorough account of the life and films of the Spanish-Basque filmmaker Julio Medem is the first book in English on the internationally renowned writer-director of Vacas, La ardilla roja (Red Squirrel), Tierra, Los amantes del Círculo Polar (Lovers of the Arctic Circle), Lucía y el sexo (Sex and Lucía), La pelota vasca: la piel contra la piedra (Basque Ball) and Caótica Ana (Chaotic Ana), Initial chapters explore Medem?s childhood, adolescence and education and examine his earliest short films and critical writings against a background of a dramatically changing Spain. Later chapters provid.